Questioning qualitative inquiry critical essays - Hammersley, Martyn. (SAGE, 2008)
Discussing 50 years of change in qualitative social research Martin Hammersley argues that the move away from natural science as a model for social inquiry involves a rejection of key principles that are essential from any commitment to research.